2021
DOI: 10.1364/boe.430935
|View full text |Cite
|
Sign up to set email alerts
|

In vivo functional imaging of the human middle ear with a hand-held optical coherence tomography device

Abstract: We describe an optical coherence tomography and vibrometry system designed for portable hand-held usage in the otology clinic on awake patients. The system provides clinically relevant point-of-care morphological imaging with 14-44 µm resolution and functional vibratory measures with sub-nanometer sensitivity. We evaluated various new approaches for extracting functional information including a multi-tone stimulus, a continuous chirp stimulus, and alternating air and bone stimulus. We also explored the vibrato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…The anterior region was thicker than the posterior region as measured with confocal microscopy 13 and optical coherence tomography 12 . Hand‐held OCT device can offer superior ease of use 24 . Low coherence interferometry is another technique used for in vivo measurements of the thickness of the TM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The anterior region was thicker than the posterior region as measured with confocal microscopy 13 and optical coherence tomography 12 . Hand‐held OCT device can offer superior ease of use 24 . Low coherence interferometry is another technique used for in vivo measurements of the thickness of the TM.…”
Section: Discussionmentioning
confidence: 99%
“…Computing the thickness of the TM is challenging because of its cone‐shaped structure. The thickness measurements at each voxel on the membrane must be taken orthogonal to the surface of the membrane 24 . From this aspect measurements based on post‐mortem specimens and sectioned TM allow easier thickness measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This flexibility opens up the possibility to image the retina of immobile/bedridden patients or infants, skin areas that are not accessible easily, ear-nose-throat measurements, or even large animals [31] and plants [32] can be imaged. In the last decade, handheld probes have proven their value in imaging the retina [33][34][35][36][37][38][39][40][41][42][43][44][45][46], hair follicles [47] and the tympanic membrane in the ear [30,48,49], to detect and monitor skin cancer [50,51] or skin and mucosal lesions [52][53][54][55][56][57][58], and as an imaging tool to assist in surgery [59,60].…”
Section: Oct Using Handheld Probes and Home/self-octmentioning
confidence: 99%
“…Here, we showed that noise exposures with intensities sufficient to produce cochlear synaptopathy also result in endolymphatic hydrops which can be detected using OCT. Although the use of OCT for cochlear imaging is currently not performed in humans, an OCT device that images the cochlea through the ear canal may allow translation of this technology to humans (Monroy et al, 2017;Kim et al, 2018b;Kim et al, 2019b;Burwood et al, 2019;Lui et al, 2021).…”
Section: Applications To Acoustic Trauma In Humansmentioning
confidence: 99%